Status Hara dan Hasil Tumpang Sari Jagung-Kedelai di Lahan Kering Lombok Utara - W. Astiko; N.M.L. Ernawati; I.P. Silawibawa (Seminar Nasional Lahan Suboptimal, 2020)
Astiko W, Ernawati NML, Silawibawa IP.  2020. Nutrient status and maize-soybean intercropping yield in dry land North Lombok. In: Herlinda S et al. (Eds.), Prosiding Semin. ar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Global warming is an increase in temperature on the surface of the earth as a result of anthropogenic activities and has an impact on climate change. In the future, agriculture will be faced with greater challenges, especially as a result of global climate change which can create an increase in the area of dry land with a more severe level of drought stress. In several regions in Indonesia, symptoms of climate change are increasingly being felt, including in dryland areas. Climate change occurring at this time can affect the productivity of maize and soybean cone juice patterns. One of the best adaptation efforts in dealing with the effects of climate change, such as changing climatic conditions and shifting seasons, is by selecting the right variety planted with a cone pattern taking into account climate conditions. Climate change affects the quality and quantity of maize-soybean cone-shaped commodity yields planted on dry land. This study aims to look for maize varieties that can adapt to high yields in soybean intercropping with a 3: 3 patern in Akar Akar Village, Bayan District, North Lombok Regency. This research used the Randomized Block Design (RBD) experimental method with 5 varieties of maize and 5 varieties of soybeans used as a treatment and repeated three times. The results showed that the maize variety Bisi 18 and Biosoy II soybean variety planted with an intercropping pattern significantly affected the soil N, P content, plant tissue, dry biomass weight, and yield to the treatment of other varieties.